2013
DOI: 10.1128/jvi.00989-13
|View full text |Cite
|
Sign up to set email alerts
|

The Rabies Virus Interferon Antagonist P Protein Interacts with Activated STAT3 and Inhibits Gp130 Receptor Signaling

Abstract: Immune evasion by rabies virus depends on targeting of the signal transducers and activator of transcription 1 (STAT1) and STAT2 proteins by the viral interferon antagonist P protein, but targeting of other STAT proteins has not been investigated. Here, we find that P protein associates with activated STAT3 and inhibits STAT3 nuclear accumulation and Gp130-dependent signaling. This is the first report of STAT3 targeting by the interferon antagonist of a virus other than a paramyxovirus, indicating that STAT3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 28 publications
6
74
0
Order By: Relevance
“…The mumps viral V protein can target STAT3 to ubiquitin-mediated degradation45 and the V protein of measles forms a complex with STAT proteins to prevent nuclear translocation46. The P protein of rabies virus associates with STAT3 in an oncostatin M- dependent manner to inhibit STAT3 activation47. STAT3 is also inhibited by the human cytomegalovirus (hCMV)48 and the human metapneumovirus (hMPV)49.…”
Section: Discussionmentioning
confidence: 99%
“…The mumps viral V protein can target STAT3 to ubiquitin-mediated degradation45 and the V protein of measles forms a complex with STAT proteins to prevent nuclear translocation46. The P protein of rabies virus associates with STAT3 in an oncostatin M- dependent manner to inhibit STAT3 activation47. STAT3 is also inhibited by the human cytomegalovirus (hCMV)48 and the human metapneumovirus (hMPV)49.…”
Section: Discussionmentioning
confidence: 99%
“…The RABV phosphoprotein (P-protein) has critical roles in genome transcription/replication and antagonism of interferon (IFN)-dependent antiviral responses (2)(3)(4)(5)(6)(7)(8)(9). In infected cells, the P gene produces full-length P-protein (P1) and several N-terminally truncated isoforms, predominantly P2 and P3, via a ribosomal leaky scanning mechanism (7,10).…”
mentioning
confidence: 99%
“…responses in the host (Randall and Goodbourn, 2008). In previous studies, RABV phosphoprotein P was confirmed to be an IFN antagonist that plays a major and multifunctional role in disturbing interferon gene expression, interferon-induced STAT signaling, and the functions of antiviral protein (Lieu et al, 2013;Vidy et al, 2007;Wiltzer et al, 2014). Although RABVs have developed advanced countermeasures against the IFN system, the interferon-mediated mechanisms are still the main factors restricting RABV replication in vivo (Carty et al, 2014;Faul et al, 2009;Schoggins et al, 2011).…”
Section: Discussionmentioning
confidence: 96%